Comparative/International Research on Women and Crime: Analysis of ASC and ESC Annual Meeting Presentations. (October 2014) - Kim, Bitna; Merlo, Alida V.
Despite the recent advocacy of comparative/international and collaborative research by the leaders in the field of criminology and criminal justice, there is uncertainty regarding how much comparative/international research on the topic of women is being conducted. Using the published abstracts of papers presented at the American Society of Criminology (ASC) Annual Meeting and the European Society of Criminology (ESC) Annual Meeting, the authors examine presentations on women and crime with a cross-cultural or international focus. The current study found that research on crime with an international or comparative focus accounted for an average 14.1% of the ASC women and crime presentations over the 12-year period, and about 24.2% of the ESC women and crime presentations over the 10-year period. With respect to comparing the topical areas of the research, domestic violence was the most prevalent topic in presentations on women and crime at both the ASC and ESC Annual Meetings, while presentations on sex crimes and trafficking occurred more frequently at the ESC Annual Meetings than the ASC Annual Meetings. The authors also discuss the role that the ASC Division of Women and Crime and the Gender, Crime and Justice Working Group of the ESC can play to encourage the study of women and crime internationally.